2004
DOI: 10.1063/1.1664022
|View full text |Cite
|
Sign up to set email alerts
|

Large second-order optical nonlinearities of fresnoite-type crystals in transparent surface-crystallized glasses

Abstract: Second-order optical nonlinearities, d33 values, of fresnoite-type crystals, Ba2TiSi2O8 (BTS), Sr2TiSi2O8 (STS), and Ba2TiGe2O8 (BTG), have been evaluated by measurements on transparent surface-crystallized glasses consisting of fresnoite-type crystals with the Maker fringe technique. It is found that all these crystals show large d33 values, i.e., d33=13±2 pm/V for BTS, d33=7.2±0.4 pm/V for STS, and d33=22±3 pm/V for BTG. In particular, it is emphasized that BTG has an extremely large d33 value, comparable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 36 publications
6
87
0
Order By: Relevance
“…17 , 18 On the other hand, according to Cabral et 20 The optical functional nanocrystallized glass based on a silicate system has a significant potential for photonic devices, fiber applications and the formation of the periodic structure of the nanocrystals. Since it is considered that the formation of a crystalline phase in glass, the SHG and PL properties are very sensitive to the heat-treatment conditions, it is of particular interest to examine the crystallization behavior of the 40BaOெ20TiO 2 ெ 40SiO 2 glass and to clarify the correlation between the SHG and PL intensities and the heat-treatment condition.…”
Section: Introductionmentioning
confidence: 99%
“…17 , 18 On the other hand, according to Cabral et 20 The optical functional nanocrystallized glass based on a silicate system has a significant potential for photonic devices, fiber applications and the formation of the periodic structure of the nanocrystals. Since it is considered that the formation of a crystalline phase in glass, the SHG and PL properties are very sensitive to the heat-treatment conditions, it is of particular interest to examine the crystallization behavior of the 40BaOெ20TiO 2 ெ 40SiO 2 glass and to clarify the correlation between the SHG and PL intensities and the heat-treatment condition.…”
Section: Introductionmentioning
confidence: 99%
“…The glasses with Gd 2 O 3 contents of 8-14 mol% have large densities of over 6 g/cm 3 and large refractive indices of w1.9. Transparent surface crystallized glasses consisting of two kinds of crystalline phases with different morphologies, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it should be pointed out that the optical secondorder non-linearity of d 33 for ferreoelectric Ba 2 TiGe 2 O 8 crystals in transparent crystallized glasses is w10 pm/V, being comparable to d 22 and d 11 of LiNbO 3 single crystal [3]. Very recently, Honma et al [4,5] 3 . Furthermore, they found that some glasses such as 12.5Sm 2 O 3 $30Bi 2 O 3 $57.5B 2 O 3 are crystallized by irradiations of a continuous Nd:YAG laser with a wavelength of lZ1064 nm, giving the formation of non-linear optical crystalline dots and lines [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations